1999
DOI: 10.1002/(sici)1097-4636(19990915)46:4<531::aid-jbm11>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermal analysis characterization of aortic tissues for cardiac valve bioprostheses

Abstract: Two multistep extractions were achieved on porcine aortic tissues to obtain acellular matrices used for cardiac bioprostheses. The evaluation of structural modifications and the possible damage of extracellular matrix fibrous proteins were investigated by means of thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Protein-water interactions and degradation temperatures were determined by TGA. DSC was used to characterize protein thermal transitions (glass transition and denaturation)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
87
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 24 publications
15
87
0
2
Order By: Relevance
“…Most collagen fibrils and elastic fibers exhibit well-preserved ultrastructural features (Figs. 7 and 8) -a situation consistent with our previous results [4][5][6] -therefore the gross distribution of collagen and elastin is left unchanged with respect to the native ECM [32]. These ultrastructural patterns are also confirmed for the human cryopreserved specimens (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Most collagen fibrils and elastic fibers exhibit well-preserved ultrastructural features (Figs. 7 and 8) -a situation consistent with our previous results [4][5][6] -therefore the gross distribution of collagen and elastin is left unchanged with respect to the native ECM [32]. These ultrastructural patterns are also confirmed for the human cryopreserved specimens (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Basically, this twostep procedure includes preparing xeno-or homogeneic valve matrices [4] with mechanical and functional properties suitable for cell engraftment. We recently set up a technique for decellularizing porcine heart valve leaflets using a non-ionic detergent, Triton X100, which enables scaffolds with an optimally preserved collagenouselastic network to be achieved [5,6]. It is particularly important to select cell type(s) suitable for an appropriate valve cell colonization in vitro in static conditions or in a bioreactor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large endothermic phenomenon is observed for the different collagen samples between 50°C and 150°C. This can be attributed to the evaporation and vaporization of residual bound water in collagen (Samouillan et al 1999). A second endothermic event is observed above 200°C for all the samples with a specific shape for each sample.…”
Section: Collagen Treatment Using Low Temperature Plasma Jet In Ambiementioning
confidence: 79%
“…The DSC method has proven to be a valuable tool in assessing the role of collagen in structural alterations of several cardiovascular and musculoskeletal diseases [8][9][10][11]. Our previous study showed that DSC was the appropriate method for investigation of subtle changes in physicochemical conditions of peritoneum using tissues obtained during surgical procedures [12].…”
Section: Introductionmentioning
confidence: 99%